Micro credit, myth manufactured : unveiling appropriation of surplus value and an icon - edited by Farooque Chowdhury; Chowdhury, Farooque (Dhaka : Shrabon Prokashani, 2007)
Contributed articles on microfinance in Bangladesh and criticism about the Grameen Bank.
Includes bibliographical references and index.
Keywords: Yunus, Muhammad, -- 1940-; Grameen Bank -- Corrupt practices; Microfinance -- Bangladesh; Poverty -- Bangladesh